El cobro de tasas, contribuciones especiales y de mejoras por parte de los Gads Municipales vulnera derechos constitucionales y legales al no existir el hecho generador por lo que se debe reformar el código tributario y el cootad - Rios Hidalgo, Leovani Patricio (2015)
This paper contains an investigation of the Tax Code and the Code of Territorial Autonomy and decentralization "THE COLLECTION OF FEES, CONTRIBUTIONS AND IMPROVEMENTS BY MUNICIPAL GADs LEGAL RIGHTS AND CONSTITUTIONAL BREACH NOT EXIST AL GENERATOR MADE BY WHAT TO REFORMING THE TAX CODE AND COOTAD”. is the same as the result of a thorough investigation regarding the proposed issue aims to present an analysis of the reality of taxation rates , special contributions or improvement as such constitutes a sample significant than has generally been the case in the collection of fees corresponding to municipalities in Ecuador , in the present study examines the process of charging fees is being conducted in a manner unsuitable mainly because it no charges for existing services , this causes discomfort taxpayers as it becomes an illegal act, since there must first be the elements necessary to meet the requirements for this area arises and therefore is chargeable according to the Constitution and the law of matter. In this work, besides the above, the most relevant aspects of the Tax Code and COOTAD stand. It was also intended to motivate the reader and invite you to reflect on the positive changes that could affect the system to levy charges for the assets subject if our conclusions, recommendations and proposals for legal reform are welcome. And the collection of taxes and fees especially by municipalities is an important issue not only for Ecuadorian law, but to the rest of Latin America, and the countries of this region bear a common history. Based on rates , tax collection , has become pitifully , and in some cases, many times in an act of inequality and charged for services without being the operative event such as tax charged for services sewer without any drainage, so the development of the law is essential to prevent such acts against the Ecuadorian government and its own people. Public administration must be more and more a planning and foresight of the effects of their decisions organization. Lack of control in the system of tax collection of municipalities fosters social inequality and generates malaise and discontent citizen. As can be seen at the beginning of this investigation a thorough review of literature that discusses the conceptual framework, the doctrinal framework and the legal framework is done. The theoretical framework is defined and conceptualized terms: Finance Law, Tax Law, State Budget revenue , tax revenues, non-tax revenue , the tax classification law, principles of tax law , tax principles , the tribute in Ecuador , classification taxes and related topics. In the doctrinal framework a brief analysis of the methods of collecting taxes is made under current law being studied. In the legal framework the different constants discussed articles in the Constitution of Ecuador, Tax Code and Code of Territorial Organization, Autonomy and Decentralization. Regarding the materials used include: newspapers, books, legal journals , legal research guide , notebook , tape recorder , camera, car , office supplies , books, computer, printer , scanner , questionnaires , among others. In the present investigation logical scientific methods were used or intended to discover or confirm the truth by certain and firm conclusions. These methods are: scientific, inductive, deductive method and the literature method. The methodology used was intended to harmonize the scientific rigor of research; specific cases also made feasible a legal proposal for reform of